Electrical energy efficiency : how electrical equipment can be specified to optimum energy efficiency to help maximise cost savings - Callcut, Vin; Chapman, David; Heathcote, Martin; Parr, Richard (Kuala Lumpur : Department of Electricity and Gas Supply Malaysia, 1997)
PSZJBL